The Influence Of Job Position, Internal Control, And Love Of Money On Indications Of Fraudulent Behavior - Laksmeita, Niken; Rohman, H. Abdul (UNIVED Press, 2026)
Fraud in the public sector is a serious problem that can undermine the integrity of the bureaucracy and public trust. This study aims to analyze the influence of job position, internal control, and love of money on indications of fraudulent behavior among local government employees. An explanatory quantitative approach was used with a survey method targeting employees from five agencies in East Kotawaringin Regency, selected using purposive sampling. Data were collected using a likert scale questionnaire and analyzed using WarpPLS based Structural Equation Modeling. The results showed that job position, internal control, and love of money had a significant positive effect on indications of fraudulent behavior. These findings indicate that the higher the position, the weaker the internal controls, and the higher the orientation toward money, the greater the tendency to commit fraud. This study contributes to the literature by providing empirical evidence from the context of local government, as well as practical implications for the formulation of more effective fraud prevention policies.